Factors associated with spontaneous stone passage in a contemporary cohort of patients presenting with acute ureteric colic: results from the Multi‐centre cohort study evaluating the role of Inflammatory Markers In patients presenting with acute ureteric Colic (MIMIC) study. (14th May 2019) - Shah, Taimur T.; Gao, Chuanyu; Peters, Max; Manning, Todd; Cashman, Sophia; Nambiar, Arjun; Cumberbatch, Marcus; Lamb, Ben; Peacock, Anthony; Van Son, Marieke J.; van Rossum, Peter S. N.; Pickard, Robert; et al.
Abstract : Objectives: To assess the relationship of white blood cell count (WBC) and other routinely collected inflammatory and clinical markers including stone size, stone position, and medical expulsive therapy use (MET), with spontaneous stone passage (SSP) in a large contemporary cohort of patients with acute ureteric colic, as there are conflicting data on the role of WBC and other inflammatory markers in SSP in patients with acute ureteric colic. Patients and methods: Multicentre retrospective cohort study coordinated by the British Urology Researchers in Surgical Training (BURST) Research Collaborative at 71 secondary care hospitals across four countries (UK, Republic of Ireland, Australia, and New Zealand). In all, 4170 patients presented with acute ureteric colic and a computed tomography confirmed single ureteric stone. Our primary outcome measure was SSP, as defined by the absence of need for intervention to assist stone passage (SP). Multivariable mixed effects logistic regression was used to explore the relationship between key patient factors and SSP. Results: In all, 2518 patients were discharged with conservative management and had further follow‐up with a SSP rate of 74% ( n  = 1874/2518). Sepsis after discharge with conservative management was reported in 0.6% ( n  = 16/2518). On multivariable analysis neither WBC, neutrophils count, nor C‐reactive protein (CRP) predicted SSP, with an adjusted odds ratio (OR) of 0.97 (95% confidence interval [CI] 0.91–1.04, P  = 0.38), 1.06 (95% CI 0.99–1.13, P  = 0.1) and 1.00 (95% CI 0.99–1.00, P  = 0.17), respectively. MET also did not predict SSP (adjusted OR 1.11, 95% CI 0.76–1.61). However, stone size and stone position were significant predictors. SSP for stones <5 mm was 89% (95% CI 87–90) compared to 49% (95% CI 44–53) for stones ≥5–7 mm, and 29% (95% CI 23–36) for stones >7 mm. For stones in the upper ureter the SSP rate was 52% (95% CI 48–56), middle ureter was 70% (95% CI 64–76), and lower ureter was 83% (95% CI 81–85). Conclusion: In contrast to the previously published literature, we found that in patients with acute ureteric colic who are discharged with initial conservative management neither WBC, neutrophil count, nor CRP, helps determine the likelihood of SSP. We also found no overall benefit from the use of MET. Stone size and position are important predictors and our present findings represent the most comprehensive SP rates for each millimetre increase in stone size from a large contemporary cohort adjusting for key potential confounders. We anticipate that these data will aid clinicians managing patients with acute ureteric colic and help guide management decisions and the need for intervention.